Atranorin inhibits NLRP3 inflammasome activation by targeting ASC and protects NLRP3 inflammasome-driven diseases - Wang Hao-yu; Lin Xi; Huang Guan-gen; Zhou Rong; Lei Shu-yue; Ren Jing; Zhang Kai-rong; Feng Chun-lan; Wu Yan-wei; Tang Wei (Acta Pharmacologica Sinica; Vol 44, No 8 (August 2023): Acta Pharmacologica Sinica, 2023)
Aberrant NLRP3 activation has been implicated in the pathogenesis of numerous inflammation-associated diseases. However, no small molecular inhibitor that directly targets NLRP3 inflammasome has been approved so far. In this study, we show that Atranorin (C19H18O8), the secondary metabolites of lichen family, effectively prevents NLRP3 inflammasome activation in macrophages and dendritic cells. Mechanistically, Atranorin inhibits NLRP3 activation induced cytokine secretion and cell pyroptosis through binding to ASC protein directly and therefore restraining ASC oligomerization. The pharmacological effect of Atranorin is evaluated in NLRP3 inflammasome-driven disease models. Atranorin lowers serum IL-1β and IL-18 levels in LPS induced mice acute inflammation model. Also, Atranorin protects against MSU crystal induced mice gouty arthritis model and lowers ankle IL-1β level. Moreover, Atranorin ameliorates intestinal inflammation and epithelial barrier dysfunction in DSS induced mice ulcerative colitis and inhibits NLRP3 inflammasome activation in colon. Altogether, our study identifies Atranorin as a novel NLRP3 inhibitor that targets ASC protein and highlights the potential therapeutic effects of Atranorin in NLRP3 inflammasome-driven diseases including acute inflammation, gouty arthritis and ulcerative colitis.